2017
DOI: 10.1002/jcla.22124
|View full text |Cite
|
Sign up to set email alerts
|

Association of hematocrit with blood pressure and hypertension

Abstract: We demonstrated the association of altered biochemical and hematological factors with hypertension supporting the value of emerging markers for early prediction of high blood pressure in prone individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 47 publications
(54 reference statements)
4
43
1
1
Order By: Relevance
“…There was a significant relationship between serum UA level and hs‐CRP in these patients, suggesting the role of inflammation in HTN process. The possible interaction between blood viscosity, inflammation, and UA, which in conjunction with high BP may have an adverse impact on endothelial function and so become a risk factors for future events, which is in line with previous observation. In particular, Puddu et al explored the association of serum UA with the incidence of coronary and cardiovascular events in an Italian population.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…There was a significant relationship between serum UA level and hs‐CRP in these patients, suggesting the role of inflammation in HTN process. The possible interaction between blood viscosity, inflammation, and UA, which in conjunction with high BP may have an adverse impact on endothelial function and so become a risk factors for future events, which is in line with previous observation. In particular, Puddu et al explored the association of serum UA with the incidence of coronary and cardiovascular events in an Italian population.…”
Section: Discussionsupporting
confidence: 69%
“…In particular, Puddu et al explored the association of serum UA with the incidence of coronary and cardiovascular events in an Italian population. They showed that increased serum UA levels and RBC was independently related with risk of CVD events in the 6‐year follow‐up of the Gubbio Study . Another study by this research group also showed the value of serum UA as a predictor of long‐term incidence of cardiovascular events and deaths .…”
Section: Discussionmentioning
confidence: 87%
“…In this regard, Emamian and associates studied 9,808 individuals with essential hypertension and found that they had spurious elevations in their hematocrits, hemoglobin levels, red cell counts, and mean corpuscular hemoglobin values [6]. Their finding is in keeping with the fact that plasma volumes A complete blood count revealed elevations in her hematocrit (packed cell volume, PCV), hemoglobin, and red blood cell count (Table 1).…”
Section: Discussionsupporting
confidence: 39%
“…In the MASHAD study, biochemical parameters (including fasting blood glucose [FBG] and lipid profiles), demographic data (including educational level, gender, and age) and medical history as well as lifestyle information (including smoking habit), anthropometric data (including waist circumference [WC], body mass index [BMI], weight, and height) and physical activity (by Self‐declaration form) were gathered by a nurse interview . The methods of biochemical measurements using an automated analyzer and blood pressure assessments using a standard mercury sphygmomanometer are described elsewhere . Participants with dyslipidemia were defined by lipid profiles, as described previously …”
Section: Methodsmentioning
confidence: 99%